Ibn Taymiyya’s views on issues of divorce in contrast to the majority of jurists in Islamic law - Ahmed, Seerwan (2019)
This study examines and investigates Ibn Taymiyya’s opinions on issues regarding divorce in Islamic law, which disagreed with the majority of jurists’ opinions. The study aims to fill an existing gap in the field of Sunnī Islamic law related to Ibn Taymiyya’s dispute with the majority of jurists regarding divorce law. In light of the available findings, it is noted that Ibn Taymiyya had opinions regarding some issues of divorce in Islamic law different to most contemporary jurists as well as those who came before him. These issues include divorce during a woman’s menstruation period, triple divorce, intoxicated divorce, divorce pronounced in angry circumstances, a father’s divorce on behalf of his young or mentally incapacitated son, a proxy divorce of a client wife, and divorce oaths. This study found that Ibn Taymiyya, in contrast to the majority of jurists, used his interpretations, understandings and knowledge when attempting to use any evidence from the Qurʾān and the Sunna. The findings show that Ibn Taymiyya’s approach to aspects of each of the principles of jurisprudential ultimately evolved into reasons that supported his disagreements with the majority of jurists. This conclusion will support the idea that Ibn Taymiyya worked as an absolute mujtahid in the later years of his life and was not personally affiliated with any particular Sunnī school of law, not even the Ḥanbalī School to which he belonged earlier in his life.